Uji Efektifitas Perasan Jahe (Zingiber officinale) Terhadap Pertumbuhan Jamur Candida albicans - Fitrotin Azizah; Dita Artanti (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2021)
Candidiasis is one of the most common infectious diseases caused by Candida sp. In 2017 the Mycology Division of Dr. Soetomo said there were 67 patients diagnosed with candidiasis. The use of natural ingredients as an alternative to traditional medicine is increasing because it is safe for consumption and does not cause side effects. One of the natural ingredients is Ginger (Zingiber officinale). The choice of using ginger juice (Zingiber officinale) is because the ingredients are easy to obtain and easy to apply by the community. This study aims to determine the antifungal effectiveness of ginger (Zingiber officinale) juice against the growth of Candida albicans. This research is experimental by doing the treatment which was repeated 4 times, namely the concentration of ginger juice 20%, 40%, 60%, 80%, 100%, negative control (aquadest) and positive control (ketoconazole). The inhibition zone examination method used the Kirby Bauer diffusion method which was characterized by the formation of a clear zone around the paper disc on MHA (Muller Hinton Agar) media. The inhibition zone formed was measured using a caliper, then the data obtained were analyzed using the Mann-Whitney test. From laboratory examination, it was found that the average diameter of inhibition formed with concentrations of 20%, 40%, 60%, 80%, and 100% was 0 mm, and the negative control (aquadest) was 0 mm. The results of statistical analysis showed that 0.05 obtained a significant value between the administration of juice concentrations of 20%, 40%, 60%, 80%, 100% and not given (negative control-aquadest) = 1,000. From these results, it was concluded that there was no significant difference between the concentrated juice of 20%, 40%, 60%, 80%, 100% and not given (negative control - distilled water)Keywords : Ginger (Zingiber officinale), Candida albicans